1987
DOI: 10.1111/j.1398-9995.1987.tb02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of antigens and allergens during shake‐culture of Aspergillus fumigatus

Abstract: The appearance of IgG and IgE binding components in the medium of shake cultures of Aspergillus fumigatus has been studied. Cultures were grown in synthetic asparagine medium at 35 degrees C and flasks harvested in duplicate 1, 2, 3, 4, 7 and 14 days after inoculation. The pH of the medium dropped from its initial value of 5.5 to pH 3, and then after 4 days gradually increased up to pH 7.5 in the 14-day medium. The weight of mycelium, after an initial peak followed by a slight decline, increased as the pH of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…In the present study, we observed fewer IgE bands in the CF extract as compared to EN spore-mycelial extract, although the number of IgG binding bands were larger in the CF extract. This was in contrast to many earlier studies that have reported greater number of allergenic proteins in CF extract of A. fumigatus and F. solani as compared to spore-mycelial extract [23,7]. Fewer allergenic bands have also been observed in CF extracts of four different strains of Alternaria tenuis as compared to their sporemycelial extracts [24].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In the present study, we observed fewer IgE bands in the CF extract as compared to EN spore-mycelial extract, although the number of IgG binding bands were larger in the CF extract. This was in contrast to many earlier studies that have reported greater number of allergenic proteins in CF extract of A. fumigatus and F. solani as compared to spore-mycelial extract [23,7]. Fewer allergenic bands have also been observed in CF extracts of four different strains of Alternaria tenuis as compared to their sporemycelial extracts [24].…”
Section: Discussioncontrasting
confidence: 54%
“…The use of peptone and other natural ingredients for preparing CF antigens have been refuted, and the use of synthetic media is suggested [11]. The CF components of A. fumigatus, Fusarium species, C. albicans, and Penicillium notatum are more potent and are easily obtained by cultivating them in the synthetic medium [23,13,7]. The growth of EN in synthetic medium was poor [1].…”
Section: Discussionmentioning
confidence: 99%
“…This paper demonstrates that the 88-kDa antigen, which has recently been purified and shown to be specific for antibody detection in aspergillosis (3), is indeed the so-called chymotryptic antigen of A. fumigatus used for the detection of specific anti-Aspergillus antibodies by immunodiffusion or counterimmunoelectrophoresis (15). The gene coding for the 88-kDa antigen was cloned and shown to contain homologies with dipeptidyl-peptidase genes.…”
mentioning
confidence: 86%
“…The chymotrypsin activity of the precipitin had been defined only on the basis of a colorimetric reaction resulting from the release of naphthol radicals from the hydrolysis of the substrate N-acetylphenylalanine naphthyl ester (NAPNE) 1 (13). Purification of the chymotryptic antigen has been attempted by affinity chromatography on ⑀-aminocaproyltryptophan methylester-agarose (14) or by immunoaffinity using rabbit antiserum directed against a precipitin band recovered from a two-dimensional immunoelectrophoresis gel (15). Preliminary gel filtration chromatography coupled to rocket immunoelectrophoresis experiments identified a fraction reactive to the specific antibody, allowing purification of this "chymotryptic" antigen to homogeneity for the first time.…”
mentioning
confidence: 99%
“…30, 31], culture conditions as medium. pH, temperature and type of culture [9,32,33], time of incuba tion [32,[34][35][36] and storage [33], Similar variations prob ably also determine the antigenic composition of other fun gal extracts. This also means that the molecular weights of A. fumigatus antigens that contain determinants in common with other moulds may vary in different preparations of A. fumigatus antigens.…”
Section: Penicilliummentioning
confidence: 99%